Attitudes and intentions toward seeking professional psychological help among Chinese healthcare workers during the COVID-19 pandemic - Huang, Ruirui; Peng, Xiaoyan; Yu, Shuai; Tian, Yumei; Gao, Chuanying (Frontiers in Psychiatry, 2023)
Background: It has been suggested that healthcare workers (HCWs) are experiencing massive stressors that threaten their mental health during the COVID-19 pandemic, but little is known about their attitudes and intentions toward seeking professional psychological help. This study aimed to investigate the attitudes and intentions of Chinese HCWs toward seeking professional psychological help during the COVID-19 pandemic and the associated factors. Methods: A total of 1224 Chinese HCWs working in hospitals were recruited online from 12 hospitals in Hunan Province in China for a survey conducted in November 2022. The Chinese version of the Attitudes Toward Seeking Professional Psychological Help Scale-Short Form (ATSPPH-SF) and the General Help-Seeking Questionnaire (GHSQ) were separately used to assess the attitudes and intentions of the respondents toward seeking professional psychological help. Demographic and socio-psychological data were collected using a self-developed questionnaire, the Perceived Social Support Scale, the Self-Stigma of Seeking Help Scale, and the Patient Health Questionnaire-9 Scale.The 1208 HCWs in the final analysis showed relatively negative attitudes and low intentions toward seeking professional psychological help during the COVID-19 pandemic. Results of the multiple linear regression analysis showed that female sex (p=0.031), experience of psychological learning (p<0.001), and social support (p<0.001) had a positive predictive effect on the attitudes of these HCWs toward seeking professional psychological help, whereas self-stigma of seeking help (p<0.001) and depressive symptoms (p<0.001) exerted negative effects. Moreover, experience of psychological learning (p=0.004) and social support (p<0.001) had a positive predictive effect on the intentions of these HCWs toward seeking professional psychological help, whereas divorced marital status (p=0.011) and self-stigma of seeking help (p<0.001) exerted negative effects.The overall attitudes and intentions of HCWs toward seeking professional psychological help were not optimistic. Effective interventions targeted at influencing factors should be formulated to promote the professional psychological help-seeking attitudes and intentions of HCWs who are at risk of developing mental health problems.